Variabilidade da evapotranspiração de referência em contraste ao uso do solo em quatro localidades Norte mato-grossense - Oliveira, Renan Gonçalves de (2018)
Brazilian agriculture, for the most part, still depends on rainfall to supply the water needs of crops and the evapotranspiration is the main means of water transferring, in the form of vapor, to the process of cloud formation and consequently, rains. Thus, the general objective is to analyze the behavior of the reference evapotranspiration and the components used to estimate it in contrast to the land use in four locations in the North of Mato Grosso state, Brazil. The main factors related to possible changes in reference evapotranspiration over a mean period of 20 years were evaluated, identifying trends for the data set studied (ETo, n, T, u2, UR and Ppt) and the correlation (r) among they. In addition, the behavior of the Aridity Index (IA) was analyzed to observe the degree of rainfall insufficiency to maintain the soil in humidity conditions suitable for plants development. To identify how significant the trends were, we used the Mann-Kendall trend analysis and Linear Regression Analysis. The Reference Evapotranspiration showed a significant trend only in the station located in the municipality of Canarana, with a negative trend, varying 8.4 mm per year. The Aridity Index, for the driest months of the year, presented values close to 1, characterizing the region as medium to high aridity. The variable that most influenced the ETo variability was the insolation.